2022
DOI: 10.1109/access.2022.3185620
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Student Dropout Rate at the Faculty of Electrical and Computer Engineering of the University of Prishtina, Kosovo, From 2001 to 2015

Abstract: This study analyzed the student dropout rate at the Faculty of Electrical and Computer Engineering (FECE) of the University of Pristina, Kosovo, from 2001 to 2015. This phenomenon is a concern for many countries, not only for students due to its emotional effects and further consequences for their university careers but also for institutions and society in general due to its broader negative impact on their authority. Over the past two decades, a significant number of students have been enrolled in these progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Despite the progress in STEM promotion in the country, several factors contribute to higher education dropouts from STEM fields, such as the inadequate integration of STEM curricula in pre-university education, insufficient teacher training for interdisciplinary courses and a lack of laboratory equipment for scientific activities (Kabashi et al, 2022).…”
Section: The Kosovo Contextmentioning
confidence: 99%
“…Despite the progress in STEM promotion in the country, several factors contribute to higher education dropouts from STEM fields, such as the inadequate integration of STEM curricula in pre-university education, insufficient teacher training for interdisciplinary courses and a lack of laboratory equipment for scientific activities (Kabashi et al, 2022).…”
Section: The Kosovo Contextmentioning
confidence: 99%
“…Further emphasizing the intricacies of student dropouts in higher education, a detailed analysis at the Faculty of Electrical and Computer Engineering of the University of Prishtina, Kosovo, from 2001 to 2015 revealed that the reasons for dropout were not predominantly influenced by socio-economic backgrounds or urban-rural divides. Instead, they were strongly tied to high school programs and academic performance in specific courses [10]. This underscores the importance of academic preparedness and the potential impact of high school curricula on university retention rates.…”
Section: Introductionmentioning
confidence: 99%